Business Competition in the Digital Era according to Business Competition Law - Elli Ruslina (Jurnal Restorasi : Hukum dan Politik, 2024)
The digital era has significantly changed business paradigms, introducing technological innovations that impact the way companies compete. This research aims to analyze the dynamics of business competition in the context of the digital era, with a focus on the perspective of business competition law. This research uses a normative legal approach. From this research, it is concluded that the economic transformation by the Internet in the digital era provides consumer efficiencies and expands online markets, but also brings competition law challenges related to data control, abuse of dominant positions, and difficulties in recognizing practices that harm competition. The KPPU's role is important, but expanding its role and improving regulations is needed to maintain balance and encourage healthy competition in Indonesia. Synergy between KPPU, companies and the Government is considered crucial to create a business environment that supports sustainable economic growth.